METHODS FOR TRANSLATING IMPLICATURES IN QUESTIONS FROM GERMAN INTO VIETNAMESE - Thuy, Le Thi Bich (VNU Journal of Foreign Studies; Vol 34 No 6DO - 10.25073/2525-2445/vnufs.4327, 2018)
This article presents the methods used when implicatures in German questions are translated into Vietnamese based on the analysis of questions with implicatures in the drama “Der Besuch der alten Dame” (The Visit/The Visit of the Old Lady) (Friedrich Dürrenmatt) and their equivalences in the translations “Bà lớn về thăm” (Pham Thi Hoai) and “Bà tỷ phú về thăm quê” (Le Chu Cau). The finding shows that the translators combined different translation methods to preserve implicatures in the original drama. The form of most questions wasn´t changed in the translations (they have question marks at the end of the sentence). The main methods are grammar transformations (eg. changing sentence structures, changing positions of components in the sentence) and semantic transformations (eg. changing style, interpreting, explaining the meaning of the words contained in the sentence, adding the adjectives at the end of the sentence to express the modal meaning, etc.). The study also shows that some questions in the original version were changed into declarative and imperative sentences. That means there were semantical transformations in the translations, namely transformation of speech act.